MUHAMMADIYAH DAN PEMBERDAYAAN MASYARAKAT ISLAM - Tampubolon, Ichwansyah (Jurnal at-Taghyir, 2018)
AbstractIn perspective of Islamic community empowerment, it can be rised the proposition that Muhammadiyah is really exist as an empowerment organization or development of the Islamic community in contemporary era. It is because of it`s roles and contributions in effort autonomously and progressifly to conduct empowerment or development of the Islamic community in Indonesia, particularly in the area of religious life, education, health, and social by making use of modern Islamic management approach.Key words: Muhammadiyah, Islamic community empowerment, mode of empowermentÂ AbstrakDalam perspektif pemberdayaan komunitas Islam, dapat dikemukakan dalil bahwa Muhammadiyah benar-benar ada sebagai organisasi pemberdayaan atau pengembangan komunitas Islam di era kontemporer. Itu karena peran dan kontribusi dalam upaya secara mandiri dan progresif untuk melakukan pemberdayaan atau pengembangan komunitas Islam di Indonesia, khususnya di bidang kehidupan agama, pendidikan, kesehatan, dan sosial dengan memanfaatkan pendekatan manajemen Islam modern.Kata kunci: Muhammadiyah, pemberdayaan komunitas Islam, mode pemberdayaan